2008
DOI: 10.1177/1545968308315597
|View full text |Cite
|
Sign up to set email alerts
|

Motor Imagery to Enhance Recovery After Subcortical Stroke: Who Might Benefit, Daily Dose, and Potential Effects

Abstract: MIT was received positively by patients, but 40% were unable to perform imagery and interindividual variations were found on motor function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 26 publications
0
87
0
7
Order By: Relevance
“…A critical appraisal of the study designs resulted in 4 studies being categorized as Level I evidence (Page, 2000;Page, Levine, & Leonard, 2005Page, Levine, Sisto, & Johnston, 2001b), 2 as Level II (Dijkerman, Ietswaart, Johnston, & MacWalter, 2004;Müller, Bütefisch, Seitz, & Hömberg, 2007), 1 as Level III (Simmons, Sharma, Baron, & Pomeroy, 2008), 6 as Level IV (Butler & Page, 2006;Crosbie, McDonough, Gilmore, & Wiggam, 2004;Hewett, Ford, Levine, & Page, 2007;Page, Levine, & Hill, 2007;Stevens & Phillips Stoykov, 2003;Yoo, Park, & Chung, 2001), and 2 as Level V (Gaggioli, Meneghini, Morganti, Alcaniz, & Riva, 2006;Page, Levine, Sisto, & Johnston, 2001a).…”
Section: Resultsmentioning
confidence: 99%
“…A critical appraisal of the study designs resulted in 4 studies being categorized as Level I evidence (Page, 2000;Page, Levine, & Leonard, 2005Page, Levine, Sisto, & Johnston, 2001b), 2 as Level II (Dijkerman, Ietswaart, Johnston, & MacWalter, 2004;Müller, Bütefisch, Seitz, & Hömberg, 2007), 1 as Level III (Simmons, Sharma, Baron, & Pomeroy, 2008), 6 as Level IV (Butler & Page, 2006;Crosbie, McDonough, Gilmore, & Wiggam, 2004;Hewett, Ford, Levine, & Page, 2007;Page, Levine, & Hill, 2007;Stevens & Phillips Stoykov, 2003;Yoo, Park, & Chung, 2001), and 2 as Level V (Gaggioli, Meneghini, Morganti, Alcaniz, & Riva, 2006;Page, Levine, Sisto, & Johnston, 2001a).…”
Section: Resultsmentioning
confidence: 99%
“…Action observation and motor imagery have been flagged as potentially useful tools in rehabilitation from stroke and other brain injuries [1,2]. Improved methods to measure brain activity, including functional magnetic resonance imagining (fMRI) and transcranial magnetic stimulation (TMS), have shown that motor imagery and observation of actions, can, when used effectively, activate the neural motor system in a way that overlaps significantly with that activated during actual movement [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies (Johnson, 2000;Simmons, et al, 2008;Sirigu, et al, 1996) also revealed that MI ability is not well preserved in all neurological patients. As such, a thorough screening of patients' MI ability is recommended to identify those patients who might not benefit from this technique, or who need additional training with this method first before using it as a training tool.…”
Section: Resultsmentioning
confidence: 99%